PENERAPAN PUPUK ORGANIK CAIR (Bahan Aktif Aspergillus sp.) BERBAHAN DASAR LIMBAH CAIR TEMPE DAN AIR KELAPA PADA TANAMAN KANGKUNG DARAT (Ipomoea reptans Poir.) - Miranty Sirappa; Umrah; Abdul Rahim Thaha (Biology Department, Mathematics and natural science, Tadulako University, 2020)
Liquid Organic fertilizer is a fertilizer produced from organic materials in the form of liquid preparations. Research on the application of liquid organic fertilizer (active ingredient Aspergillus sp.) is based on liquid waste of Tempe and coconut water on the Kangkung land plant (Ipomoea reptans Poir.), this research has been conducted in March to November 2018 in the village Langaleso, Dolo subdistrict, Sigi Regency, Biotechnology Laboratory of Biology Department of Mathematics and Natural Sciences of Tadulako University. This research aims to observe the growth of plant Kangkung post application of liquid organic fertilizer (active ingredient Aspergillus sp.). The research designed in the complete random plan (RAL) consists of seven types and five times the replay. Composition of treatment; P0 (without the application of POC, control), P1 (Application of POC 2.5%), P2 (Application of POC 5%), P3 (Application of POC 7.5%), P4 (Application of POC 210%), P5 (Application of POC 12.5%), P6 (NPK application, without POC). Description POC Liquid Organic fertilizer (active ingredient Aspergillus sp.). The observation results showed the best growth on the implementation of P1 based on the fresh weight of the heading (8.47 g), the fresh weight of biomass (6.02 g), the fresh weight of the leaves (4.66 strands), the fresh weight of the roots (5.72 g). The P2 is based on the root length (27.10 cm). P4 treatment based on the high average plant (27.34 cm), the number of leaves (14.90 strands), dry weight of the roots (1.61 g). P6 treatment based on leaf dry weight (2.07 g).